Role of the Aspergillus-Specific IgG and IgM Test in the Diagnosis and Follow-Up of Chronic Pulmonary Aspergillosis - Li, Hongxing; Rui, Yuwen; Zhou, Wei; Liu, Lulu; He, Binchan; Shi, Yi; Su, Xin (Frontiers in Microbiology, 2019)
Background Chronic pulmonary aspergillosis (CPA) has a high rate of misdiagnosis and has been reported to have an increasing rate of morbidity and mortality.In this article, we assessed the serumAspergillus-specific IgG and IgM test in the diagnosis of patients with CPA. Methods A prospective study was conducted from January 2016 to July 2017 in Nanjing Jinling Hospital. Serum samples were collected from CPA patients (178 sera, 82 patients) and from non-aspergillosis patients (125 sera) with community-acquired pneumonia(CAP), active tuberculosis, bronchiectasis or lung tumors. Additionally, we included a control group of healthy patients(50 sera). Aspergillus-specific antibody detection was performed using a Dynamiker ELISA kit, and the results were compared with the value of galactomannan (GM) in bronchoalveolar lavage fluid (BALF). Results The sensitivity and specificity of the Aspergillus-specific IgG antibody in the diagnosis of CPA were 84.1% and 89.6%, respectively. These values were slightly higher compared to those obtained for the sensitivity and specificity using the BALF GM test(79.1% and 84.2%, respectively). However, the sensitivity and specificity of Aspergillus-specific IgM antibody were only 43.9% and 87.2%, respectively. Moreover, the positive rate of IgG in patients with subacute invasive aspergillosis (SAIA) was 87%, compared to the positive rates of IgG in CPA patients sick for 3–6months (80.0%), 6–9 months (81.8%) and ≥9 months(80.0%). Meanwhile, the positive rate of IgM in SAIA patients was 63%, compared to 46.7%, 0% and 0%for CPA patients sick for 3–6months, 6–9 months and ≥9 months, respectively. Furthermore, serum IgG levels decreased gradually in the majority of CPA patients who showed positive response to anti-fungal therapy, and IgG levels increased in two CPA patients when their disease worsened. Importantly, we noted three patients within creased IgM levels during the disease remission period. Conclusions A serum Aspergillus-specific IgG test is a valuable tool for the serologic diagnosis of CPA and SAIA, while an Aspergillus-specific IgM test is only modestly specific for the diagnosis of SAIA. Overall, the Aspergillus-specific IgG test is more valuable compared to IgM for the treatment duration monitoring.